B cells and the humoral response in melanoma: The overlooked players of the tumor microenvironment. (3rd April 2017) - Chiaruttini, Giulia; Mele, Silvia; Opzoomer, James; Crescioli, Silvia; Ilieva, Kristina M.; Lacy, Katie E.; Karagiannis, Sophia N.
ABSTRACT: Evidence of tumor-resident mature B cell and antibody compartments and reports of associations with favorable prognosis in malignant melanoma suggest that humoral immunity could participate in antitumor defense. Likely striving to confer immunological protection while being subjected to tumor-promoting immune tolerance, B cells may engender multiple functions, including antigen processing and presentation, cytokine-mediated signaling, antibody class switching, expression and secretion. We review key evidence in support of multifaceted immunological mechanisms by which B cells may counter or contribute to malignant melanoma, and we discuss their potential translational implications. Dissecting the contributions of tumor-associated humoral responses can inform future treatment avenues.